Investigation of fuel consumption of non‐scheduled trains thermal traction - Juraška, Mindaugas; Magyla, Tomas (Transport, 2004)
This article deals with the calculation of fuel consumption of trains with unpredicted scheduling (non‐scheduled trains). The need for such investigation was stimulated by the fact that because of many operational and technical reasons when trains lag behind their original schedule and further train routing becomes unscheduled and unpredicted, quite considerable amount of fuel is lost for unexpected train stopping and speeding to reach the previous original running speed. Theoretical approach is presented in this article with the estimation of train‐track interaction and resistance factors. The object of this research has typical characteristics of an ordinary train with a thermal locomotive 2T310M which weights 276 tons and 50 wagons, each of them weighting 40 t. Calculated results are presented for different running scenarios. First Published Online: 27 Oct 2010